LA AUTORÍA EN LA TRADUCCIÓN: A PROPÓSITO DE LA TRADUCCIÓN AL ESPAÑOL DE WOMAN & LABOUR DE OLIVE SCHREINER - Luis Silva-Villar; Susana Silva Villar (European Scientific Journal, ESJ, 2015)
A close inspection of the first Spanish translation of Woman and Labour (Olive Schreiner, 1911) by Flora Osete (La mujer y el trabajo, 1914) leads us to research the circumstances that brought about its publication. The concept of authorship is revisited as well as the apparent fraud created by the substitution of the translator's name.